KOMUNIKASI MASSA DALAM PROGRAM NTV MORNING: RESPONS STASIUN TV NTV TERHADAP TANTANGAN KONVERGENSI MEDIA - Dedy Zebua; Suardin Ndruru; Veronika Setyadji (JOURNAL SAINS STUDENT RESEARCH, 2026)
The transformation of digital technology has fundamentally changed the pattern of mass communication, from a one-way linear model to a two-way interactive model. This change requires broadcasters not only to convey information through television broadcasts but also to be able to adapt to the behavior of digital audiences who access information through various online platforms. In this context, Nusantara TV, through its NTV Morning program, faces the challenge of media convergence, which requires the integration of technology, content, and distribution strategies across channels. This study aims to analyze how the NTV Morning program responds to the challenges of media convergence through the implementation of a multiplatform production strategy. The study uses a qualitative approach with data collection techniques such as observation, in-depth interviews, documentation, and triangulation. The research informants consist of three key parties directly involved in the production of the NTV Morning program. The study found that the production process of the NTV Morning program takes place in three main stages: pre-production, production, and post-production, which are carried out simultaneously and collaboratively. This program implements the convergence of technology, content, and industry, and develops a distribution strategy based on an analysis of digital trends and audience preferences on television, YouTube, TikTok, Instagram, WhatsApp Channel, Facebook, and X (Twitter). NTV Morning not only upholds the principles of conventional journalism but also integrates one-way and two-way mass communication practices. This makes the program an adaptive news production model relevant to the digital media ecosystem.